The Role Of Interactive Simulations And Virtual Laboratories In The Context Of Digital Education - Gozaloy Juramirzayevna Mamatova (International Journal of Pedagogics, 2025)
This article demonstrates that the use of interactive simulations and virtual laboratories in the modern educational process deepens students’ theoretical knowledge, enhances the visualization of complex physical processes, and enables the effective organization of laboratory activities.